DESCRIPTION OF STUDENT SATISFACTION LEVEL AGAINST THE METHOD HYBRID LEARNING AT STIKES KARSA HUSADA GARUT - Hidayat, Dian Roslan; Rohadi, Dandi; Syswianti, Desy; Ramdani, Hasbi Taobah (Jurnal Medika Cendikia, 2023)
Over time, the number of Covid - 19 cases has decreased in several regions of Indonesia. This has caused several institutions to implement new policies to switch to hybrid learning methods, systems that use technology to integrate offline and online learning. Hybrid learning refers to a combination of face-to-face learning and online learning that forms a learning approach. Learning methods hybrid learning involving several factors, including students, lecturers, and networks. lecturers and students must understand the technology needed for hybrid learning, they also need to have a stable network to carry out hybrid learning methods so that students can avoid being left behind in the learning process. It is students in addition to adjusting to hybrid learning, students also still have to complete various coursework in order to get good grades and graduate on time, with changes in lecture methods that will affect the level of student satisfaction in the learning process. This research method is a quantitative research with the research design chosen is Quantitative Descriptive. In this study, quantitative descriptive was used to determine "Description of the Level of Student Satisfaction with the Method Hybrid Learning at STIKes Karsa Husada Garut”. The results showed that most of the respondents were in the satisfied category, namely 74 respondents (77.9%). Based on the research results it can be concluded that the level of student satisfaction with the hybrid learning method in STIKes Karsa Husada Garut most of them are in the satisfied category.